2012
DOI: 10.1016/j.chc.2012.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Developmental Appropriateness of Treatment for Depression in Youth: Integrating the Family in Treatment

Abstract: Youth depression is an impairing and frequently recurrent and persistent disorder that impacts current and later development, resulting in high social and economic costs. Depression and interpersonal stress are frequently transactional, with depression powerfully negatively impacting relationships and relationship stress negatively impacting the course and outcome of depression. In this context, treatment models for youth depression that emphasize interpersonal functioning, particularly family relationships, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 96 publications
0
17
0
Order By: Relevance
“…23 Family-focused interventions also have the advantage of approaching critical issues of the child's context, emerging as a promising strategy in recent years, especially in young children. 5,24 On the path to define the best treatment option for depression, the Improving the Mood with Psychoanalytic and Cognitive Therapies (IMPACT) trial is an ongoing study that is planned to recruit 540 individuals to compare effectiveness and define superiority in reducing relapse among three approaches, combined with the use of fluoxetine as needed: CBT, short term psychoanalytic therapy, and specialist clinical care. 25 Children and adolescents appear to show a response pattern different from that observed in adults with respect to antidepressants -both in terms of efficacy and adverse effects (Table 1).…”
Section: Treatmentmentioning
confidence: 99%
“…23 Family-focused interventions also have the advantage of approaching critical issues of the child's context, emerging as a promising strategy in recent years, especially in young children. 5,24 On the path to define the best treatment option for depression, the Improving the Mood with Psychoanalytic and Cognitive Therapies (IMPACT) trial is an ongoing study that is planned to recruit 540 individuals to compare effectiveness and define superiority in reducing relapse among three approaches, combined with the use of fluoxetine as needed: CBT, short term psychoanalytic therapy, and specialist clinical care. 25 Children and adolescents appear to show a response pattern different from that observed in adults with respect to antidepressants -both in terms of efficacy and adverse effects (Table 1).…”
Section: Treatmentmentioning
confidence: 99%
“…As aforementioned, TADS found that the addition of CBT to medication management alleviated the increased suicide risk. There is increasing evidence for psychotherapy, particularly for family-based interventions (95). For example, attachmentbased family therapy (ABFT) was first developed to reduce depression and suicidal ideation (96).…”
Section: Management Of Depression and Suicidality In Adolescents In Pmentioning
confidence: 99%
“…Two major national trials in the United States (TADS, TORDIA), one large trial in the United Kingdom (ADAPT) and several smaller studies document the benefits associated with current psychosocial and pharmacologic treatments for depression in adolescents (For review, interested readers are referred to…(Tompson et al, 2012, Sakolsky and Birmaher, 2012, Birmaher et al, 2007). Cognitive-behavior therapy (CBT), Interpersonal Psychotherapy (IPT), and Attachment-Based Family Therapy for adolescent depression have documented efficacy and other promising treatment strategies are under development and expanding to younger children (Tompson et al, 2012, Kovacs et al, 2006, Kennard et al, 2008, Lenze et al, 2011).…”
Section: Are We Ready? Do We Have Interventions For Youth Depressimentioning
confidence: 99%